2012
DOI: 10.1177/0021998312451609
|View full text |Cite
|
Sign up to set email alerts
|

Drilling of polymer matrix composites: A review

Abstract: This article addresses the effects of drilling parameters on the machinability parameters in drilling polymeric composite materials. Drilling parameters include: feed, speed, drill wear, drill geometry, drilling with special tools, and composite materials parameters. The machinability parameters include: thrust force, torque, residual strength, surface roughness, and mechanical and thermal damages of the composite materials. Delamination associated with drilling processes can often be the limiting factor for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(78 citation statements)
references
References 63 publications
0
78
0
Order By: Relevance
“…It was also noted that tool-wear, high trust force, and torque that eventually affect the quality of produced hole are also considered as issues that need to be addressed [2][3][4][5]. In the literature, various cutting speeds [6], feed rate [3,7], drill bit geometries [8][9][10][11], tool coatings [12,13], and tool materials [14,7] have been proposed to minimize delamination in drilling of CFRP composite materials. Although it was reported that a majority of studies presented in the literature did not use any coolant and lubrication during drilling of CFRP composites [15], a few studies reported the positive effects of cooling and lubrication such as flood cooling [16] and MQL on drilling performance of this particular work material [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It was also noted that tool-wear, high trust force, and torque that eventually affect the quality of produced hole are also considered as issues that need to be addressed [2][3][4][5]. In the literature, various cutting speeds [6], feed rate [3,7], drill bit geometries [8][9][10][11], tool coatings [12,13], and tool materials [14,7] have been proposed to minimize delamination in drilling of CFRP composite materials. Although it was reported that a majority of studies presented in the literature did not use any coolant and lubrication during drilling of CFRP composites [15], a few studies reported the positive effects of cooling and lubrication such as flood cooling [16] and MQL on drilling performance of this particular work material [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although up to this stage, the temperature maxima was below T g of the CFRP, it may still lower the strength of the composites in the thickness direction [43,44] which could affect the drilling qualities. As such, it is believed that the existing mathematic models in CFRP machining (e.g., the popular critical thrust force models [3]) could be further refined for better damage prediction and control if the temperature characteristics derived from this study can be taken into account. The temperature began to fluctuate after passing its peak (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, CFRP belongs to hard-tomachine materials and is particularly sensitive to high temperatures. The machining process of CFRP is typically performed in a dry condition, as traditional coolants usually interact with CFRP physically and/ or chemically, leading to undesirable machining errors and weakened material bearing capacity [2][3][4]. Due to its low thermal conductivity and low specific heat capacity, heat can easily accumulate in CFRP cutting zone in the absence of coolant.…”
mentioning
confidence: 99%
See 2 more Smart Citations